Carbohydrate components of pomace in corn-based extrudates: interactions, expansion dynamics, and structure-texture relationships - Karkle, Elisa Noemberg Lazzari (Kansas State University, 2011)
Extrusion processing is a technology widely used to make ready-to-eat snack and breakfast cereal products. The raw materials that result in optimal texture and consumer acceptance are mainly those with high levels of starch, which greatly limits the nutritional value of these products. One alternative to enhance the nutritional value is the incorporation of fruits and vegetables. Fruits and vegetables are consistently under-consumed by the American population and incorporation into extruded products may help increase the intake of important nutrients, such as dietary fiber. In the first part of this study a lab-scale twin screw extruder was used for processing directly expanded products based on corn flour and apple pomace (0-28%), resulting in a total dietary fiber content of 1.1-22.5%. Apple pomace increased nucleation and favored axial expansion. The change in cell size and alignment explained the higher mechanical resistance caused by apple pomace. The objective of the second part was to study the effect of preconditioning regimen on the extent of matrix transformation and impact on texture, microstructure and digestibility. The material was processed on a pilot scale extruder. The results showed that increasing the opportunity for hydration increased starch gelatinization at all pomace levels. Apple pomace promoted milder extrusion conditions, resulting in less starch gelatinization and solubilization and reduced starch digestibility. Digestibility was also affected by structure, with a strong correlation between the available starch fraction and cell wall thickness/cell size ratio (r=0.90). The third part of this study was designed to gain a better understanding of the impact of the individual cell wall components (cellulose, lignin, xyloglucan and pectin) on expansion and structure formation. The results suggest that compatibility with starch is critical for good dispersion in the matrix, therefore good expansion and structure forming properties.
Keywords: Extrusion; Fiber; Food Science (0359)